Incremental training intensities increases loads on the lower back of elite female rowers - Buckeridge, E. M.; Bull, A. M. J.; McGregor, A. H. (Journal of Sports Sciences, 2016)
Lumbar-pelvic kinematics change in response to increasing rowing stroke rates, but little is known about the effect of incremental stroke rates on changes in joint kinetics and their implications for injury. The purpose of this study was to quantify the effects of incremental rowing intensities on lower limb and lumbar-pelvic kinetics. Twelve female rowers performed an incremental test on a rowing ergometer. Kinematic data of rowers` ankle, knee, hip and lumbar-pelvic joints, as well as external forces at the handle, seat and foot-stretchers of the rowing machine were recorded. Inter-segmental moments and forces were calculated using inverse dynamics and were compared across stroke rates using repeated measures ANOVA. Rowers exhibited increases in peak ankle and L5/S1 extensor moments, reductions in peak knee moments and no change in peak hip moments, with respect to stroke rate. Large shear and compressive forces were seen at L5/S1 and increased with stroke rate (P < 0.05). This coincided with increased levels of lumbar-pelvic flexion. High levels of lumbar-pelvic loading at higher stroke rates have implications with respect to injury and indicated that technique was declining, leading to increased lumbar-pelvic flexion. Such changes are not advantageous to performance and can potentially increase the risk of developing injuries.